Illustrative cases of fraud in a bank: types, causes, distresses and mitigators / Surida Mat Piah - Mat Piah, Surida (2013)
The purpose of this study is to examine the types, causes, distresses and mitigations of bank fraud. From the findings of this study, it can be concluded that the purpose of the study are met. The summary of the findings are as follows: 1. Types of fraud in the bank are categorised into external and internal fraud. 2. The causes of the occurrence of frauds in the bank that were found in this study are mainly due to violation of standard operating procedures, breach of dual control, lack of monitoring and supervision from the superior, negligence act and dishonesty of the employees. 3. Due to the fraud, the distresses that were found in this study and suffered by the bank are not only in terms of financial loss and non-financial loss. 4. The internal control systems of the bank are found to be able to detect fraud and can be considered as effective but there is still a loophole in the system that the bank needs to address. From the above findings, the recommendations for this study are as below: 1. Provides training to employees to instil fraud awareness culture. 2. Conducting fraud awareness campaign and fraud alert. 3. Provide training on good ethics. 4. Perform anti-fraud control gap analysis. 5. Improve the internal control systems of the bank. 6. Revisit the bank fraud risk management framework. 7. Screening on the background of future or potential staff. 8. Tone at the top, management by example. 9. Provide financial assistance or solution to employees’ financial problems 10. Imposed strict disciplinary action against offenders. 11. Provide hotlines and encourage whistleblowing